Blockade of the purinergic P2Y(12) receptor greatly increases the platelet inhibitory actions of nitric oxide - Kirkby, Nicholas S. (National Academy of Sciences, 2013)
Circulating platelets are constantly exposed to nitric oxide (NO) released from the vascular endothelium. This NO acts to reduce platelet reactivity, and in so doing blunts platelet aggregation and thrombus formation. For successful hemostasis, platelet activation and aggregation must occur at sites of vascular injury despite the constant presence of NO. As platelets aggregate, they release secondary mediators that drive further aggregation. Particularly significant among these secondary mediators is ADP, which, acting through platelet P2Y(12) receptors, strongly amplifies aggregation. Platelet P2Y(12) receptors are the targets of very widely used antithrombotic drugs such as clopidogrel, prasugrel, and ticagrelor. Here we show that blockade of platelet P2Y(12) receptors dramatically enhances the antiplatelet potency of NO, causing a 1,000- to 100,000-fold increase in inhibitory activity against platelet aggregation and release reactions in response to activation of receptors for either thrombin or collagen. This powerful synergism is explained by blockade of a P2Y(12) receptor-dependent, NO/cGMP-insensitive phosphatidylinositol 3-kinase pathway of platelet activation. These studies demonstrate that activation of the platelet ADP receptor, P2Y(12), severely blunts the inhibitory effects of NO. The powerful antithrombotic effects of P2Y(12) receptor blockers may, in part, be mediated by profound potentiation of the effects of endogenous NO.